Playout buffer control for cbr traffic - Klimo, Martin (Communications - Scientific letters of the University of Zilina, 2000)
Networks based on the packet switching principle introduce a new type of the continuous signal distortion which is caused by a random delay of packets. To eliminate this distortion, playout buffers are introduced. The paper presents a method how to evaluate the rest of this distortion in terms of Signal-to-Noise Ratio, when static policy is used for sample rate control in the case of CBR traffic.